The Social Lives of Figurines: Recontextualizing the Third-Millennium-BC Terracotta Figurines from Harappa - Sharri Clark (Les Carnets de l’ACoSt)
This book is a critical examination of representations of the body in the Indus civilization, focusing on the anthropomorphic terracotta figurines from Harappa and using more flexible notions of sex, gender, and sexuality to explore Indus conceptions of sexual difference as it relates to other aspects of social difference and identity.